The effects of a single bout of high intensity exercise on stress reactivity, mind wandering, and lecture comprehension in young adults - Anisa Morava; Ali Shirzad; James Van Riesen; Mustafa Shirzad; Nader Elshawish; Erind Alushaj; Harry Prapavessis (PLoS ONE, 2025)
Post-secondary students experience acute stressors daily. Acute stress has been associated with poor cognitive and learning outcomes. Prior work has demonstrated a single bout of exercise can attenuate acute stress responses. The present study examined the effects of a single 30-minute bout of high intensity aerobic exercise on multidimensional stress reactivity and learning-related outcomes. Forty participants were randomized to either engaging in an exercise bout or seated rest. Participants were then exposed to the Trier Social Stress Test followed by a 20-minute video lecture. The video lecture contained embedded mind wandering probes. Acute exercise did not attenuate stress responses, however promoted greater on-task behaviour (i.e., less mind wandering) and improved lecture comprehension scores. Notably, state anxiety was positively associated with mind wandering and mind wandering was negatively associated with lecture comprehension. Collectively, examining the role of acute interventions that reduce state anxiety may promote favourable learning outcomes in young adults.